The Gravity, The Levity: Let Us Speak of Tactile Encounters - Fayen d'Evie; Georgina Kleege (Disability Studies Quarterly, 2018)
This paper will describe an artist-curatorial project by Fayen d'Evie and Georgina Kleege, working with the collection of the KADIST Art Foundation in San Francisco to investigate the radical potential of haptic criticism and tactile dialogue.